Understanding trust and perceived usefulness in the consumer acceptance of an e-service: a longitudinal investigation. Issue 2 (1st February 2017) - Mou, Jian; Shin, Dong-Hee; Cohen, Jason
ABSTRACT: E-services remain characterised by uncertainty despite their proliferation. Consumer trust beliefs are therefore considered an important determinant of e-service adoption. However, the research has not yet considered the potentially dynamic nature of these trust beliefs or how early-stage trust might influence later-stage adoption and use. To address this gap, this study draws on the theory of reasoned action and expectation–confirmation theory in a longitudinal study of trust in e-services. We examine how trust interacts with other consumer beliefs such as perceived usefulness (PU) and how these beliefs together influence consumer intentions and behaviours concerning e-services at both the initial and latter stages of use. The empirical context is online health information services. Data collection on a student population occurred during two time periods approximately five weeks apart. The results show that PU and trust are important at both the initial and latter stages in the consumer acceptance of online health services. Consumers' actual usage experiences modify perceptions of usefulness and influence the confirmation of their initial expectations. These results have implications for our understanding of the dynamic nature of trust and PU as well as their roles in the long-term sustainability of e-services.